2023
DOI: 10.1007/s12369-023-00968-4
|View full text |Cite
|
Sign up to set email alerts
|

Not Only WEIRD but “Uncanny”? A Systematic Review of Diversity in Human–Robot Interaction Research

Abstract: Critical voices within and beyond the scientific community have pointed to a grave matter of concern regarding who is included in research and who is not. Subsequent investigations have revealed an extensive form of sampling bias across a broad range of disciplines that conduct human subjects research called “WEIRD”: Western, Educated, Industrial, Rich, and Democratic. Recent work has indicated that this pattern exists within human–computer interaction (HCI) research, as well. How then does human–robot interac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 232 publications
(307 reference statements)
1
6
0
Order By: Relevance
“…We found that non-WEIRD populations were rarely sampled in XAI user research. This finding matches results from studies that explored sampling in HCI and HRI and report that 73-75% of papers tested only WEIRD populations (Linxen et al, 2021;Seaborn et al, 2023). However, our results suggest that the problem may be worse in XAI research, as more than 80% of XAI papers with relevant information involved only WEIRD participants.…”
Section: General Discussion and Recommendationssupporting
confidence: 89%
See 3 more Smart Citations
“…We found that non-WEIRD populations were rarely sampled in XAI user research. This finding matches results from studies that explored sampling in HCI and HRI and report that 73-75% of papers tested only WEIRD populations (Linxen et al, 2021;Seaborn et al, 2023). However, our results suggest that the problem may be worse in XAI research, as more than 80% of XAI papers with relevant information involved only WEIRD participants.…”
Section: General Discussion and Recommendationssupporting
confidence: 89%
“…Our findings fill a significant gap in previous studies in HCI and HRI that reported generalizability problems related to WEIRD sampling in these fields (Linxen et al, 2021;Seaborn et al, 2023). This is because these studies did not measure the scope of the generalizations that researchers produced thus leaving it unclear whether methodological shortcomings were involved.…”
Section: General Discussion and Recommendationsmentioning
confidence: 50%
See 2 more Smart Citations
“…For instance, do "caring masculinities" look the same in a South Asian WhatsApp group chat compared to a British one? We should be cautious about making assumptions and leaning on generalizations from WEIRD research at CHI [121] and adjacent spaces, such as HRI [234]. Still, HCI is a radical, creative, and political space, welcoming of inclusive knowledge and change in praxis.…”
Section: Bringing In Masculinities From the Extant Literaturementioning
confidence: 99%